2018
DOI: 10.1155/2018/6935054
|View full text |Cite
|
Sign up to set email alerts
|

Heart in Acromegaly: The Echocardiographic Characteristics of Patients Diagnosed with Acromegaly in Various Stages of the Disease

Abstract: To determine whether the echocardiographic presentation allows for diagnosis of acromegalic cardiomyopathy. 140 patients with acromegaly underwent echocardiography as part of routine diagnostics. The results were compared with the control group comprising of 52 age- and sex-matched healthy volunteers. Patients with acromegaly presented with higher BMI, prevalence of arterial hypertension, and glucose metabolism disorders (i.e., diabetes and/or prediabetes). In patients with acromegaly, the following findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 30 publications
2
33
0
10
Order By: Relevance
“…These findings are consistent with other studies. Popielarz-Grygalewicz et al ( 21 ) also noted significant LA enlargement in acromegalic patients (LAVI 41.4 vs. 29.9 ml/m 2 ; p < 0.001).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These findings are consistent with other studies. Popielarz-Grygalewicz et al ( 21 ) also noted significant LA enlargement in acromegalic patients (LAVI 41.4 vs. 29.9 ml/m 2 ; p < 0.001).…”
Section: Discussionmentioning
confidence: 83%
“…Both of these pose a risk of LV diastolic and systolic dysfunction. Recent studies have shown impaired LV systolic function in acromegalic patients assessed using both standard methods and new echocardiography methods such as speckle-tracking echocardiography ( 21 , 22 ). In our study, the ACRO group presented a higher LV mass, impaired LV systolic function, and mitral annulus velocity (e′).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these results were not confirmed by Volschan et al, who did not reveal strain impairment [25]. The end stage of acromegaly cardiomyopathy is characterized by ventricular dilatation with systolic dysfunction [26,27]. This is a rare condition, but some cases have been reported in the literature, including in some younger patients [28,29].…”
Section: Introductionmentioning
confidence: 79%
“…La mayoría de las series evalúan los diferentes componentes de la ECV con ultrasonido 32 . En años recientes se ha empleado la resonancia magnética nuclear cardiaca (RMC); en estos estudios se informa una menor prevalencia de hipertrofia de ventrículo izquierdo y de fibrosis miocárdica, lo que hace suponer que los estudios ecocardiográficos sobreestiman su frecuencia.…”
Section: Enfermedades Cardiovascularesunclassified